UPAH DAN LINGKUNGAN KERJA KAITANNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Harti, ; Siti Anisah, (Pendidikan Ekonomi, 2010)
The current research was conducted to examine the influence of wage and working environment on the work productivity of the employees of Batik Tulis Gedog UD. Budi Karya Kerek Tuban. The study was a quantitative research. The sample was the whole population, consisting of40 permanent employees of UD. Budi Karya Kerek Tuban. The data were collected from documentation and questionnaires. Multiple linier regression was used in the data analysis.  The result of the study showed that there was a significant influence of the wage and working environment on the work productivity. The wage was the most dominant factor affecting the employees productivity.